2006
DOI: 10.1093/pcp/pci216
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function of Abscisic Acid in the Regulation of Rice (Oryza sativa L.) Root Growth and Development

Abstract: Plant roots retain developmental plasticity and respond to environmental stresses or exogenous plant growth regulators by undergoing profound morphological and physiological alteration. In this study, we investigated the effects of exogenous ABA on root growth and development in Taichung native 1 (TN1) rice. Exogenous application of 10 microM ABA leads to swelling, root hair formation and initiation of lateral root primodia in the tips of young, seminal rice roots. Cortex cells increased in size and were irreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 40 publications
7
83
0
7
Order By: Relevance
“…It is important to note that shorter roots are the consequence of reduced growth rate in the elongation zone rather than in the cell division zone (Sharp et al, 2004;Yamaguchi et al, 2010). We have observed that ABA treatment also leads to shorter and more branched roots, which is consistent with previously published work (Chen et al, 2006). Our findings that ABA treatment restricts RePRP expression in the root elongation zone and not in the division zone suggest that RePRPs may be responsible for the inhibitory effect of ABA/stress on root elongation.…”
Section: Reprps Are Localized To the Plasma Membranesupporting
confidence: 92%
See 1 more Smart Citation
“…It is important to note that shorter roots are the consequence of reduced growth rate in the elongation zone rather than in the cell division zone (Sharp et al, 2004;Yamaguchi et al, 2010). We have observed that ABA treatment also leads to shorter and more branched roots, which is consistent with previously published work (Chen et al, 2006). Our findings that ABA treatment restricts RePRP expression in the root elongation zone and not in the division zone suggest that RePRPs may be responsible for the inhibitory effect of ABA/stress on root elongation.…”
Section: Reprps Are Localized To the Plasma Membranesupporting
confidence: 92%
“…In addition, the root length increase of the maize (Zea mays) vp mutant was significantly lower than that in the wild type under water deficit conditions, indicating that ABA is required for maintaining rather than completely repressing root development under water stress (Sharp, 2002;Sharp and LeNoble, 2002). The effects of ABA application on rice root have been observed to include the swelling of young root tips, abundant formation of root hairs, and initiation of lateral roots close to tips (Chen et al, 2006). These morphological changes require the involvement of calmodulin and de novo protein synthesis, but the mechanism is still unclear.…”
mentioning
confidence: 99%
“…ABA inhibited shoot growth and had no effect on root growth with an increase of lateral root number in the absence of Pb, whereas 10 mg L −1 ABA treatment promoted root and inhibited shoot growth. Previous studies have shown that exogenous ABA usually inhibits shoot growth, but maintains or even promotes root growth when applied to nonstressed rice (Chen et al 2006) and Cynanchum komarovii (Yang et al 2007) seedlings, but a few studies report that exogenous ABA can increase shoot growth. The stimulatory effects of ABA on shoot growth might be the result of a combination of improved cell extensibility and stimulated cell division attributable to arrest at the G1 phase of the cell cycle since cell development in the G1 phase is closely linked to shoot growth (Finkelstein et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous ABA increased the formation of lateral roots. This may be due to the fact that ABA may transmit a Ca 2+ signal to cells in the epidermis and vascular cylinder either directly or indirectly, to alter cell fates (Chen et al 2006). Under lead stress, 2.5 mg L −1 ABA significantly increased root dry mass, R/S, and the number of lateral roots compared with Pb treatments alone, indicating that 2.5 mg L −1 ABA application partially counteracted the inhibitory effects of Pb on plant growth (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation